Impact of National Security Challenge in Development Prospect of South Asia - Jha, Shikha (Unity Journal, 2022)
National security has always been viewed as a precondition for sustainable economic, political, and social development. Any sort of challenges or threats upon national security directly infringes the developmental course. South Asia, has been rampantly facing security-related challenges and obstructions as terrorism, counter-terrorism, militarization, and religious extremism, civil war, and border disputes. Such challenges have not only jeopardized the peace within the region but a seething unrest has been pounded in the development process. This paper primarily focuses on national security challenges faced by countries in South Asia. South Asian nations resort to increment of defense budget, militarization, border security, and struggle for nuclear power to address their security challenge. I have examined the impact of such response upon the course of development in this paper. This is a qualitative research and refers to secondary source of data which includes; books, journals, reports of reputed institutes and think tanks. The analysis finds that increasing militarization and defense budget has been abysmal to address national security threat in South Asia. South Asian nations can resort to bilateral talks and diplomatic measure to address their security threats. This will save larger economic resources which could be utilized for development prospect.